Many gods and many voices the role of the prophet in English and American modernism - Martz, Louis Lohr 1913-2001 (Univ. of Missouri Press, 1998)
In Many Gods and Many Voices distinguished scholar Louis L. Martz addresses works by Ezra Pound, T.S. Eliot, William Carlos Williams, H.D., and D.H. Lawrence, with brief treatment of the relation of Pound's Cantos to Joyce's Ulysses. Martz argues that a prophetic tradition is represented in the Cantos, The Waste Land, Paterson, and H.D.'s Trilogy and Helen in Egypt, along with Lawrence's The Plumed Serpent and the second version of Lady Chatterley's Lover. Martz's premise is that biblical prophecy, with its mingling of poetry and prose, its abrupt shifts from violent denunciation to exalted poetry, provides a precedent for the texture of these modernist works that will help readers to appreciate the mingling of "voices" and the complex mixture of elements. Examining their interrelationships and their common themes, Many Gods and Many Voices offers fresh insights into these modern writers.
Keywords: Lawrence, D. H <1885-1930> - (David Herbert) - Personnages - Prophètes; Lawrence, D. H <1885-1930> -- (David Herbert) -- Characters -- Prophets; Geschichte 1900-2000; Geschichte 1900-1940; Geschichte 1900-1965; Dieux dans la littérature; Modernisme (Littérature) - Grande-Bretagne; Modernisme (Littérature) - États-Unis; Poésie américaine - 20e siècle - Histoire et critique; Prophètes dans la littérature; Prophéties dans la littérature; Religion et littérature; American poetry -- 20th century -- History and criticism; Gods in literature; Modernism (Literature) -- English-speaking countries; Prophecies in literature; Prophets in literature; Religion and literature -- English-speaking countries; Lyrik; Englisch; Prophetie; Literatur; USA